Simplified versus standard regimen for focal radiofrequency ablation of dysplastic Barrett's oesophagus: a multicentre randomised controlled trial. (August 2018) - Pouw, Roos E; Künzli, Hannah T; Bisschops, Raf; Sondermeijer, Carine M; Koch, Arjun D; Didden, Paul; Gotink, Anniek W; Schoon, Erik J; Curvers, Wouter L; Bergman, Jacques J G H M; Weusten, Bas L A M
Summary: Background: For focal radiofrequency ablation of Barrett's oesophagus, a simplified regimen (3 × 15 J/cm 2, without cleaning) has proven to be as effective as the standard regimen (2 × 15 J/cm 2, followed by cleaning, followed by 2 × 15 J/cm 2 ). However, this simplified regimen seemed to be associated with a higher stenosis rate. Therefore, we lowered the radiofrequency energy and hypothesised that this new simplified regimen would be as effective and safe as the standard regimen. Methods: This randomised non-inferiority trial included patients with dysplastic Barrett's oesophagus or residual Barrett's oesophagus after endoscopic resection or circumferential radiofrequency ablation, in five European tertiary referral centres. Patients were randomly assigned (1:1) to the new simplified regimen (3 × 12 J/cm 2, without cleaning) or the standard regimen, with variable block sizes of four, six, and eight patients, stratified by participating hospital. Focal radiofrequency ablation was done every 3 months, up to a maximum of three treatments, until all Barrett's oesophagus was eradicated. The primary outcome was complete endoscopic and histological regression of dysplasia and intestinal metaplasia after two focal radiofrequency ablation treatments, assessed in the intention-to-treat population. Non-inferiority was assessed on the basis of the difference between groups in the median percentage of Barrett's oesophagus surface regression, with a non-inferiority margin of −15%. This study is registered withwww.trialregister.nl, number NTR4994, and is completed. Findings: Between March 25, 2015, and July 25, 2016, 84 patients were randomly assigned to treatment: 44 to receive the simplified regimen and 40 to receive the standard regimen. One patient assigned to the simplified regimen and four assigned to the standard regimen were excluded because they weree found not to be eligible; therefore the final intention-to-treat population consisted of 43 patients in the simplified ablation group and 36 in the standard ablation group. Complete endoscopic and histological regression of dysplasia and intestinal metaplasia after two focal radiofrequency ablation treatments was achieved in 32 (74%, 95% CI 59–87) patients treated with the simplified protocol, versus 30 (83%, 95% CI 67–94) patients treated with the standard protocol (p=0·34). Median Barrett's oesophagus surface regression after two focal radiofrequency ablation sessions was 98% (IQR 95–100) in the simplified regimen group and 100% (97–100) in the standard regimen group. The difference between medians was 2% (95% CI −0·562 to 3·162); thus the simplified regimen was deemed non-inferior to the standard regimen. Stenoses requiring dilatation were observed in four (9%) of 43 patients in the simplified regimen group and four (11%) of 36 in the standard regimen group. Post-procedural bleeding requiring repeat endoscopy occurred in one (2%) patient in the simplified ablation group and three (8%) patients in the standard ablation group. One patient (2%) in the simplified treatment group died 36 days after the second radiofrequency ablation procedure, due to an unknown cause. Interpretation: Based on the results of this study, we conclude that the simplified regimen is the preferred regimen for focal radiofrequency ablation of Barrett's oesophagus. Funding: None.